2007
DOI: 10.1021/ja070441j
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Bonding of Gold Nanoparticles on a H-terminated Si(100) Substrate Obtained by Electro- and Electroless Deposition

Abstract: Dome-shaped gold nanoparticles (with an average diameter of 10.5 nm) are grown on H-terminated Si(100) substrates by simple techniques involving electro- and electroless deposition from a 0.05 mM AuCl3 and 0.1 M NaClO4 solution. XPS depth profiling data (involving Au 4f core-level and valence band spectra) reveal for the first time the formation of gold silicide at the interface between the Au nanoparticles and Si substrate. UV-visible diffuse reflectance spectra indicate that both samples have surface plasmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 42 publications
9
57
0
Order By: Relevance
“…Peaks A1 and A2 are attributed to the formation of two gold nitride phases (Siller et al 2005), while peak B is associated with InN (Kumar et al 2010). The Au 4f core levels show a shift to higher BE by about 0.92 eV for InN NRs sample, which also indicates the formation of gold nitride phase (Zhao et al 2007).…”
Section: Resultsmentioning
confidence: 91%
“…Peaks A1 and A2 are attributed to the formation of two gold nitride phases (Siller et al 2005), while peak B is associated with InN (Kumar et al 2010). The Au 4f core levels show a shift to higher BE by about 0.92 eV for InN NRs sample, which also indicates the formation of gold nitride phase (Zhao et al 2007).…”
Section: Resultsmentioning
confidence: 91%
“…In the Figure a, the spectra of Au 4f region from NPG was fitted with two Gaussian peaks. It exhibited an intense Au 4f 7/2 (Au 4f 5/2 ) peak at 84.7 eV (88.4 eV), which is 0.8 eV higher in binding energy (BE) than that of bulk metallic Au but only 0.3 eV lower than that of gold silicide . It suggested that the NPG structure was a mixture of metallic gold and gold silicide.…”
Section: Resultsmentioning
confidence: 99%
“…The crystallographic identifications of all the Au peaks are labeled, and it exhibited identical patterns as those reported earlier. 35 Figure 4(a) compares the corresponding Au 4f XPS spectra as a function of the total sputtering time for Au NPs obtained by 30 min synthesis with 1 wt. % HAuCl 4 solution.…”
Section: A Reductive Synthesis Of Au Nps On the Pvsz Surfacementioning
confidence: 99%